Acceptance Analysis of BRI Mobile Banking (BRIMO) using The Technology Acceptance Model (Study Case: Student at UPN Veteran Jawa Timur) - Erista Maya Safitri; M. Novianto Anggoro; Firman Perdana; Achmad Yusuf Al Ma'ruf (International Journal of Computer, Network Security and Information System, 2023)
BRIMO mobile service ranks first in the number of transactions. However, in its use, there are still many obstacles experienced by users. This study aims to determine the level of user acceptance of BRIMO using the Technology Acceptance Model (TAM) approach. This study used the TAM framework: perceived usefulness, perceived ease of use, attitude to use, behavioral intention, behavior, and experience. The study was conducted on users of the BRIMO application by UPN Veterans East Java students using a purposive non-probability sampling technique, obtaining 100 respondents. The data type used is primary data obtained directly from respondents. Methods of data collection using a questionnaire. Methods of data analysis using the Partial Least Square (PLS) statistical test approach and Bootstrapping. The results showed that Perceived Ease Of Use affected perceived usefulness. , Perceived Usefulness influences Behavior, Experience Affects Perceived Ease of Use, and Experience Affects Perceived Usefulness. The implications of the results of this study are input for banks to continue to improve mobile banking services in order to increase the number of mobile banking application users